Sosial Media pada Pendidikan Indonesia: Pengaruh Inovasi Media Sosial Terhadap Kualitas Pelajar di Indonesia - Lailita, Nabila Aulia; Khoirunnisa, Nabilla Velia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Technological advancements that continue to evolve have resulted in various innovations aimed at facilitating human work, creating sophisticated devices, and providing ease in communication. This article reviews how social media innovations can influence the quality of students in Indonesia. The aim is to understand the positive and negative impacts of social media. This research employs a qualitative method that involves descriptive data collection using references from the literature, reading, note-taking, and analyzing information sourced from the Google Scholar platform. The results of the research indicate that rapid technological development has comprehensively changed human life, with social media being one of its main aspects. Although it provides ease of interaction and broadens knowledge, social media also presents challenges, particularly related to the behavior and morals of students